Analysis of Financial distress at PT Bank Perkreditan Rakyat Artha Kramat. - Umi Masulah; Liris Kristina; Iip Dyah Kusumaningati (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2025)
The number of rural banks in Indonesia has decreased every year. The depreciation of the number of rural banks is also inseparable from unstable financial performance. Financial statement analysis is needed to review if there are characteristics of bankruptcy characterized by the company experiencing financial distress or financial difficulties. The Zmijewski method is a bankruptcy prediction model using ratio analysis that measures the performance of leverage (solvency) and liquidity of a company. The purpose of this study is to analyze financial performance using profitability, solvency, liquidity, and financial distress ratios using the Zmijewski method calculation at Â Bank Perkreditan Rakyat Artha Kramat during 2020-2023. The research method used is quantitative descriptive, where data collection techniques are carried out by observation, literature study, and documentation obtained from secondary data. The results showed that based on the analysis of profitability and solvency ratios, BPR Artha Kramat's financial performance was in the bad category because it did not meet the standard criteria. However, based on the analysis of liquidity ratios and the Zmijewski method, BPR Artha Kramat is indicated to be in a healthy or good condition and has no potential to experience financial distress.Keywords:, profitability ratio analysis, solvency, liquidity, financial distress, Zmijewski method